Engaging Socially Vulnerable Communities and Communicating About Climate Change–Related Risks and Hazards - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Extreme weather events exacerbated by climate change can compound existing vulnerabilities and inequities experienced by socially vulnerable people including pregnant people, children, low-income populations, Indigenous populations, immigrant groups, the elderly, people with disabilities, vulnerable occupation groups, communities of color, and people with preexisting or chronic medical conditions. Decision makers need to adopt strategies for engaging these communities on an ongoing basis to inform and empower individual decision making, identify and understand local concerns, and provide the necessary resources. This rapid expert consultation highlights how decision makers can continuously engage with vulnerable communities, as well as communicate risk and promote adaptation in the face of extreme weather events exacerbated by climate change. Implementing this guidance can help decision makers, researchers, and communities work collaboratively, linking analysis, deliberation, and program design to best adapt to climate change-related hazards and risks.

Building Capacity for Teaching Engineering in K-12 Education - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Engineering education is emerging as an important component of US K-12 education. Across the country, students in classrooms and after- and out-of-school programs are participating in hands-on, problem-focused learning activities using the engineering design process. These experiences can be engaging; support learning in other areas, such as science and mathematics; and provide a window into the important role of engineering in society. As the landscape of K-12 engineering education continues to grow and evolve, educators, administrators, and policy makers should consider the capacity of the US education system to meet current and anticipated needs for K-12 teachers of engineering. Building Capacity for Teaching Engineering in K-12 Education reviews existing curricula and programs as well as related research to understand current and anticipated future needs for engineering-literate K-12 educators in the United States and determine how these needs might be addressed. Key topics in this report include the preparation of K-12 engineering educators, professional pathways for K-12 engineering educators, and the role of higher education in preparing engineering educators. This report proposes steps that stakeholders - including professional development providers, postsecondary preservice education programs, postsecondary engineering and engineering technology programs, formal and informal educator credentialing organizations, and the education and learning sciences research communities - might take to increase the number, skill level, and confidence of K-12 teachers of engineering in the United States.

Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Teachers play a critical role in the success of their students, both academically and in regard to long term outcomes such as higher education participation and economic attainment. Expectations for teachers are increasing due to changing learning standards and a rapidly diversifying student population. At the same time, there are perceptions that the teaching workforce may be shifting toward a younger and less experienced demographic. These actual and perceived changes raise important questions about the ways teacher education may need to evolve in order to ensure that educators are able to meet the needs of students and provide them with classroom experiences that will put them on the path to future success. Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace explores the impact of the changing landscape of K-12 education and the potential for expansion of effective models, programs, and practices for teacher education. This report explores factors that contribute to understanding the current teacher workforce, changing expectations for teaching and learning, trends and developments in the teacher labor market, preservice teacher education, and opportunities for learning in the workplace and in-service professional development.

Climate Change, the Indoor Environment, and Health - Institute of Medicine (The National Academies Press, 2011)
The indoor environment affects occupants' health and comfort. Poor environmental conditions and indoor contaminants are estimated to cost the U.S. economy tens of billions of dollars a year in exacerbation of illnesses like asthma, allergic symptoms, and subsequent lost productivity. Climate change has the potential to affect the indoor environment because conditions inside buildings are influenced by conditions outside them. Climate Change, the Indoor Environment, and Health addresses the impacts that climate change may have on the indoor environment and the resulting health effects. It finds that steps taken to mitigate climate change may cause or exacerbate harmful indoor environmental conditions. The book discusses the role the Environmental Protection Agency (EPA) should take in informing the public, health professionals, and those in the building industry about potential risks and what can be done to address them. The study also recommends that building codes account for climate change projections; that federal agencies join to develop or refine protocols and testing standards for evaluating emissions from materials, furnishings, and appliances used in buildings; and that building weatherization efforts include consideration of health effects. Climate Change, the Indoor Environment, and Health is written primarily for the EPA and other federal agencies, organizations, and researchers with interests in public health; the environment; building design, construction, and operation; and climate issues.

Birth Settings in America: Outcomes, Quality, Access, and Choice - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The delivery of high quality and equitable care for both mothers and newborns is complex and requires efforts across many sectors. The United States spends more on childbirth than any other country in the world, yet outcomes are worse than other high-resource countries, and even worse for Black and Native American women. There are a variety of factors that influence childbirth, including social determinants such as income, educational levels, access to care, financing, transportation, structural racism and geographic variability in birth settings. It is important to reevaluate the United States' approach to maternal and newborn care through the lens of these factors across multiple disciplines. Birth Settings in America: Outcomes, Quality, Access, and Choice reviews and evaluates maternal and newborn care in the United States, the epidemiology of social and clinical risks in pregnancy and childbirth, birth settings research, and access to and choice of birth settings.

STEM Integration in K-12 Education: Status, Prospects, and an Agenda for Research - National Academy of Engineering; National Research Council (The National Academies Press, 2014)
STEM Integration in K-12 Education examines current efforts to connect the STEM disciplines in K-12 education. This report identifies and characterizes existing approaches to integrated STEM education, both in formal and after- and out-of-school settings. The report reviews the evidence for the impact of integrated approaches on various student outcomes, and it proposes a set of priority research questions to advance the understanding of integrated STEM education. STEM Integration in K-12 Education proposes a framework to provide a common perspective and vocabulary for researchers, practitioners, and others to identify, discuss, and investigate specific integrated STEM initiatives within the K-12 education system of the United States. STEM Integration in K-12 Education makes recommendations for designers of integrated STEM experiences, assessment developers, and researchers to design and document effective integrated STEM education. This report will help to further their work and improve the chances that some forms of integrated STEM education will make a positive difference in student learning and interest and other valued outcomes.

Himalayan Glaciers: Climate Change, Water Resources, and Water Security - National Research Council (The National Academies Press, 2012)
Scientific evidence shows that most glaciers in South Asia's Hindu Kush Himalayan region are retreating, but the consequences for the region's water supply are unclear, this report finds. The Hindu Kush Himalayan region is the location of several of Asia's great river systems, which provide water for drinking, irrigation, and other uses for about 1.5 billion people. Recent studies show that at lower elevations, glacial retreat is unlikely to cause significant changes in water availability over the next several decades, but other factors, including groundwater depletion and increasing human water use, could have a greater impact. Higher elevation areas could experience altered water flow in some river basins if current rates of glacial retreat continue, but shifts in the location, intensity, and variability of rain and snow due to climate change will likely have a greater impact on regional water supplies. Himalayan Glaciers: Climate Change, Water Resources, and Water Security makes recommendations and sets guidelines for the future of climate change and water security in the Himalayan Region. This report emphasizes that social changes, such as changing patterns of water use and water management decisions, are likely to have at least as much of an impact on water demand as environmental factors do on water supply. Water scarcity will likely affect the rural and urban poor most severely, as these groups have the least capacity to move to new locations as needed. It is predicted that the region will become increasingly urbanized as cities expand to absorb migrants in search of economic opportunities. As living standards and populations rise, water use will likely increase-for example, as more people have diets rich in meat, more water will be needed for agricultural use. The effects of future climate change could further exacerbate water stress. Himalayan Glaciers: Climate Change, Water Resources, and Water Security explains that changes in the availability of water resources could play an increasing role in political tensions, especially if existing water management institutions do not better account for the social, economic, and ecological complexities of the region. To effectively respond to the effects of climate change, water management systems will need to take into account the social, economic, and ecological complexities of the region. This means it will be important to expand research and monitoring programs to gather more detailed, consistent, and accurate data on demographics, water supply, demand, and scarcity.

Abrupt Impacts of Climate Change: Anticipating Surprises - National Research Council
Climate is changing, forced out of the range of the past million years by levels of carbon dioxide and other greenhouse gases not seen in the Earth's atmosphere for a very, very long time. Lacking action by the world's nations, it is clear that the planet will be warmer, sea level will rise, and patterns of rainfall will change. But the future is also partly uncertain2014there is considerable uncertainty about how we will arrive at that different climate. Will the changes be gradual, allowing natural systems and societal infrastructure to adjust in a timely fashion? Or will some of the changes be more abrupt, crossing some threshold or \

Attribution of Extreme Weather Events in the Context of Climate Change - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
As climate has warmed over recent years, a new pattern of more frequent and more intense weather events has unfolded across the globe. Climate models simulate such changes in extreme events, and some of the reasons for the changes are well understood. Warming increases the likelihood of extremely hot days and nights, favors increased atmospheric moisture that may result in more frequent heavy rainfall and snowfall, and leads to evaporation that can exacerbate droughts. Even with evidence of these broad trends, scientists cautioned in the past that individual weather events couldn't be attributed to climate change. Now, with advances in understanding the climate science behind extreme events and the science of extreme event attribution, such blanket statements may not be accurate. The relatively young science of extreme event attribution seeks to tease out the influence of human-cause climate change from other factors, such as natural sources of variability like El Niño, as contributors to individual extreme events. Event attribution can answer questions about how much climate change influenced the probability or intensity of a specific type of weather event. As event attribution capabilities improve, they could help inform choices about assessing and managing risk, and in guiding climate adaptation strategies. This report examines the current state of science of extreme weather attribution, and identifies ways to move the science forward to improve attribution capabilities.

Understanding Climate Change Feedbacks - National Research Council (The National Academies Press, 2003)
During the past decade, scientists have learned much about the complex natural processes that influence climate variability and change, and our ability to model climate has increased significantly. We also have begun to better identify those parts of the climate system that are particularly important and not well understood and that therefore limit our ability to project the future evolution of Earth's climate. One of these critical areas is our understanding of the role of feedbacks in the climate system and their role in determining climate sensitivity. Feedbacks are processes in the climate system that can either amplify or dampen the system's response to changed forcings. This study looks at what is known and not known about climate change feedbacks and seeks to identify the feedback processes most in need of improved understanding. It identifies key observations needed to monitor and understand climate feedbacks, discusses ways to evaluate progress in understanding climate feedbacks, recommends ways to improve climate modeling and analysis for climate feedbacks research, and identifies priority areas for research.

Advancing the Science of Climate Change - National Research Council (The National Academies Press, 2010)
Climate change is occurring, is caused largely by human activities, and poses significant risks for2014and in many cases is already affecting2014a broad range of human and natural systems. The compelling case for these conclusions is provided in Advancing the Science of Climate Change, part of a congressionally requested suite of studies known as America's Climate Choices. While noting that there is always more to learn and that the scientific process is never closed, the book shows that hypotheses about climate change are supported by multiple lines of evidence and have stood firm in the face of serious debate and careful evaluation of alternative explanations. As decision makers respond to these risks, the nation's scientific enterprise can contribute through research that improves understanding of the causes and consequences of climate change and also is useful to decision makers at the local, regional, national, and international levels. The book identifies decisions being made in 12 sectors, ranging from agriculture to transportation, to identify decisions being made in response to climate change. Advancing the Science of Climate Change calls for a single federal entity or program to coordinate a national, multidisciplinary research effort aimed at improving both understanding and responses to climate change. Seven cross-cutting research themes are identified to support this scientific enterprise. In addition, leaders of federal climate research should redouble efforts to deploy a comprehensive climate observing system, improve climate models and other analytical tools, invest in human capital, and improve linkages between research and decisions by forming partnerships with action-oriented programs.

Adapting to the Impacts of Climate Change - National Research Council (The National Academies Press, 2010)
Across the United States, impacts of climate change are already evident. Heat waves have become more frequent and intense, cold extremes have become less frequent, and patterns of rainfall are likely changing. The proportion of precipitation that falls as rain rather than snow has increased across the western United States and Arctic sea ice has been reduced significantly. Sea level has been rising faster than at any time in recent history, threatening the natural and built environments on the coasts. Even if emissions of greenhouse gases were substantially reduced now, climate change and its resulting impacts would continue for some time to come. To date, decisions related to the management and protection of the nation's people, resources, and infrastructure have been based on records in the recent past, when climate was relatively stable. Adapting to the Impacts of Climate Change, part of the congressionally requested America's Climate Choices suite of studies, calls for a new paradigm-one that considers a range of possible future climate conditions and impacts that may be well outside the realm of past experience. Adaptation requires actions from many decision makers in federal, state, tribal, and local governments; the private sector; non-governmental organizations; and community groups. However, current efforts are hampered by a lack of solid information about the benefits, costs, and effectiveness of various adaptation options; climate information on regional and local scales; and a lack of coordination. Adapting to the Impacts of Climate Change calls for a national adaptation strategy that provides needed technical and scientific resources, incentives to begin adaptation planning, guidance across jurisdictions, shared lessons learned, and support of scientific research to expand knowledge of impacts and adaptation.

National Security Implications of Climate Change for U.S. Naval Forces - National Research Council (The National Academies Press, 2011)
In response to the Chief of Naval Operations (CNO), the National Research Council appointed a committee operating under the auspices of the Naval Studies Board to study the national security implications of climate change for U.S. naval forces. In conducting this study, the committee found that even the most moderate current trends in climate, if continued, will present new national security challenges for the U.S. Navy, Marine Corps, and Coast Guard. While the timing, degree, and consequences of future climate change impacts remain uncertain, many changes are already underway in regions around the world, such as in the Arctic, and call for action by U.S. naval leadership in response. The terms of reference (TOR) directed that the study be based on Intergovernmental Panel on Climate Change (IPCC) scenarios and other peer-reviewed assessment. Therefore, the committee did not address the science of climate change or challenge the scenarios on which the committee's findings and recommendations are based. National Security Implications of Climate Change for U.S. Naval Forces addresses both the near- and long-term implications for U.S. naval forces in each of the four areas of the TOR, and provides corresponding findings and recommendations. This report and its conclusions are organized around six discussion areas2014all presented within the context of a changing climate.

Monitoring Progress Toward Successful K-12 STEM Education: A Nation Advancing? - National Research Council (The National Academies Press, 2013)
Following a 2011 report by the National Research Council (NRC) on successful K-12 education in science, technology, engineering, and mathematics (STEM), Congress asked the National Science Foundation to identify methods for tracking progress toward the report's recommendations. In response, the NRC convened the Committee on an Evaluation Framework for Successful K-12 STEM Education to take on this assignment. The committee developed 14 indicators linked to the 2011 report's recommendations. By providing a focused set of key indicators related to students' access to quality learning, educator's capacity, and policy and funding initiatives in STEM, the committee addresses the need for research and data that can be used to monitor progress in K-12 STEM education and make informed decisions about improving it. The recommended indicators provide a framework for Congress and relevant deferral agencies to create and implement a national-level monitoring and reporting system that: assesses progress toward key improvements recommended by a previous National Research Council (2011) committee; measures student knowledge, interest, and participation in the STEM disciplines and STEM-related activities; tracks financial, human capital, and material investments in K-12 STEM education at the federal, state, and local levels; provides information about the capabilities of the STEM education workforce, including teachers and principals; and facilitates strategic planning for federal investments in STEM education and workforce development when used with labor force projections. All 14 indicators explained in this report are intended to form the core of this system. Monitoring Progress Toward Successful K-12 STEM Education: A Nation Advancing? summarizes the 14 indicators and tracks progress towards the initial report's recommendations.

Ecological Impacts of Climate Change - National Research Council (The National Academies Press, 2008)
The world's climate is changing, and it will continue to change throughout the 21st century and beyond. Rising temperatures, new precipitation patterns, and other changes are already affecting many aspects of human society and the natural world. In this book, the National Research Council provides a broad overview of the ecological impacts of climate change, and a series of examples of impacts of different kinds. The book was written as a basis for a forthcoming illustrated booklet, designed to provide the public with accurate scientific information on this important subject.

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.

Review of the Draft Fifth National Climate Assessment - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Roughly every four years, the U.S. Global Change Research Program produces a congressionally mandated assessment of global change science and the impacts, adaptation, and mitigation of climate change in the United States. The draft Fifth National Climate Assessment (NCA5), released publicly in November 2022, covers a wide range of U.S. impacts, from human health and community well-being to the built environment, businesses and economies, and ecosystems and water resources. NCA5 had the largest scale of collaboration to date in the series, with input from hundreds of experts from all levels of governments, academia, non-government organizations, the private sector, and the public. The National Academies report provides an independent, comprehensive review and makes recommendations to strengthen the accuracy, credibility, and accessibility of the draft NCA5 report. The National Academies2019 review of the draft NCA5 report finds that it successfully meets the requirements of the federal mandate, provides accurate information, and effectively communicates climate science to the public, decision makers, and other stakeholders. The review makes recommendations for ways the draft NCA5 report could be strengthened, including: adopting more clear and consistent structure for key messages and figures across the report; resolving inconsistencies between chapters in how terms and topics are discussed, for example the use of scenarios and projections; intentionally applying an equity and justice lens across chapters; and increasing emphasis on certain topical areas.

Restructuring Federal Climate Research to Meet the Challenges of Climate Change - National Research Council (The National Academies Press, 2009)
Climate change is one of the most important global environmental problems facing the world today. Policy decisions are already being made to limit or adapt to climate change and its impacts, but there is a need for greater integration between science and decision making. This book proposes six priorities for restructuring the United States' climate change research program to develop a more robust knowledge base and support informed responses: Reorganize the Program Around Integrated Scientific-Societal Issues Establish a U.S. Climate Observing System Support a New Generation of Coupled Earth System Models Strengthen Research on Adaptation, Mitigation, and Vulnerability Initiate a National Assessment of the Risks and Costs of Climate Change Impacts and Options to Respond Coordinate Federal Efforts to Provide Climate Information, Tools, and Forecasts Routinely to Decision Makers

Abrupt Climate Change: Inevitable Surprises - National Research Council (The National Academies Press, 2002)
The climate record for the past 100,000 years clearly indicates that the climate system has undergone periodic2014and often extreme2014shifts, sometimes in as little as a decade or less. The causes of abrupt climate changes have not been clearly established, but the triggering of events is likely to be the result of multiple natural processes. Abrupt climate changes of the magnitude seen in the past would have far-reaching implications for human society and ecosystems, including major impacts on energy consumption and water supply demands. Could such a change happen again? Are human activities exacerbating the likelihood of abrupt climate change? What are the potential societal consequences of such a change? Abrupt Climate Change: Inevitable Surprises looks at the current scientific evidence and theoretical understanding to describe what is currently known about abrupt climate change, including patterns and magnitudes, mechanisms, and probability of occurrence. It identifies critical knowledge gaps concerning the potential for future abrupt changes, including those aspects of change most important to society and economies, and outlines a research strategy to close those gaps. Based on the best and most current research available, this book surveys the history of climate change and makes a series of specific recommendations for the future.

Informing an Effective Response to Climate Change - National Research Council (The National Academies Press, 2010)
Global climate change is one of America's most significant long-term policy challenges. Human activity2014especially the use of fossil fuels, industrial processes, livestock production, waste disposal, and land use change2014is affecting global average temperatures, snow and ice cover, sea-level, ocean acidity, growing seasons and precipitation patterns, ecosystems, and human health. Climate-related decisions are being carried out by almost every agency of the federal government, as well as many state and local government leaders and agencies, businesses and individual citizens. Decision makers must contend with the availability and quality of information, the efficacy of proposed solutions, the unanticipated consequences resulting from decisions, the challenge of implementing chosen actions, and must consider how to sustain the action over time and respond to new information. Informing an Effective Response to Climate Change, a volume in the America's Climate Choices series, describes and assesses different activities, products, strategies, and tools for informing decision makers about climate change and helping them plan and execute effective, integrated responses. It discusses who is making decisions (on the local, state, and national levels), who should be providing information to make decisions, and how that information should be provided. It covers all levels of decision making, including international, state, and individual decision making. While most existing research has focused on the physical aspect of climate change, Informing an Effective Response to Climate Change employs theory and case study to describe the efforts undertaken so far, and to guide the development of future decision-making resources. Informing an Effective Response to Climate Change offers much-needed guidance to those creating public policy and assists in implementing that policy. The information presented in this book will be invaluable to the research community, especially social scientists studying climate change; practitioners of decision-making assistance, including advocacy organizations, non-profits, and government agencies; and college-level teachers and students.